Professional standards and the social licence to operate: a panacea for finance or an exercise in symbolism?. (2nd October 2015) - O'Brien, Justin; Gilligan, George; Roberts, Alex; McCormick, Roger
Abstract : This paper considers how the use of professional practice is applied in Australia and the United Kingdom via the lens of professionalism in the finance sector. How can effective conduct standards, training or ethical commitment be established and maintained? What is the potential of the social licence to operate (SLTO), which is emerging as the preferred strategy of the Bank of England? We argue that the SLTO model has enormous traction for the finance industry, not just in the United Kingdom. It has global applicability. To work effectively, however, the assessment has to be outside of the sector itself and voluntarily accepted by it.